Four new quinolizidine alkaloids from the flowers of Sophora viciifolia. (April 2020) - Gao, Dan-Dan; Zhang, Zhi-Jun; Li, Hong-Mei; Chen, Xuan-Qin; Liu, Dan; Li, Rong-Tao
Graphical abstract: Highlights: Four new quinolizidine alkaloids were isolated from Sophora viciifolia . The structures of new compounds were elucidated by NMR and HR-ESI-MS analysis. Anti-inflammatory and anti-influenza virus activities of isolates were evaluated. Abstract: Four new quinolizidine alkaloids, including three matrine-type alkaloids, 8 α -hydroxysophocarpine (1 ), 13 β -hydroxyoxymatrine (2 ), 9 α -acetoxymatrine (3 ), and one sparteine-type alkaloid, 14 β -hydroxylupanine (4 ), together with four known ones, were isolated from the flowers of Sophora viciifolia . Their structures were elucidated by extensive spectroscopic methods including 1D-, 2D-NMR, and HR-ESI-MS. All of the isolates were evaluated for their anti-inflammatory and anti-influenza virus activities. Unfortunately, none of them were active towards these assays.